DINAMIKA PEMBERIAN HARTA WARIS LEBIH KEPADA ANAK BUNGSU DI JAKARTA TIMUR - Aziz, Abdul (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2024)
This study examines the practice of giving more inheritance to the youngest children in East Jakarta, by highlighting the influence of legal and cultural factors. The background of this research is driven by differences in understanding in the practice of inheritance distribution, which can result in injustice and disputes in the future. The research method used is a qualitative approach, involving in-depth interviews with seven informants who have varying levels of understanding of inheritance law. The findings of the study show that a limited understanding of Islamic inheritance law and customary law plays a major role in the decision to give more property to the youngest child. Factors such as family burdens, sibling willingness, and family traditions contributed to the decision. On the other hand, informants who have a deeper understanding associate the division of property with the responsibility and contribution of the youngest child in the family. This study recommends the need for more comprehensive counseling on the principles of inheritance law so that the distribution of assets can be carried out fairly and in accordance with applicable legal and customary provisions, reducing the potential for disputes in the future. Keywords: Youngest child; Customary law; Islamic inheritance law; East Jakarta; Distribution of inheritance